EVOLUŢIA INSTITUŢIILOR EDUCAŢIONALE EVREIEŞTI ÎN IMPERIUL RUS. CAZUL BASARABIEI - Roitman, Alexandru (Lexon-Prim, 2023)
Education in the Jewish community has always held an important place. The Jewish education system has a long history. Its religious nature has contributed significantly to the preservation of the Jewish people and the perpetuation of their customs and traditions. Education for the Jewish population has always been not only a form of self-organization but also a way of transmitting the collective religious mentality. In this article, we aim to analyze several aspects of the evolution of Jewish education in the Russian Empire, as well as its particularities for the Jewish community in Bessarabia. We will describe the legislation and reforms that influenced the functioning of these educational institutions during the 19th century in the Russian Empire.
The evolution of Jewish educational institutions in the Russian Empire: the case of Bessarabia
Keywords: education; Jewish community; Jewish education system; Bessarabia; Russian Empire